The Effect of Tannin-Rich Witch Hazel on Growth of Probiotic Lactobacillus plantarum - Reuven Rasooly; Alex C. Howard; Naomi Balaban; Bradley Hernlem; Emmanouil Apostolidis (MDPI AG, 2022)
Probiotic bacteria help maintain microbiome homeostasis and promote gut health. Maintaining the competitive advantage of the probiotics over pathogenic bacteria is a challenge, as they are part of the gut microbiome that is continuously exposed to digestive and nutritional changes and various stressors. Witch hazel that is rich in hamamelitannin (WH, whISOBAXTM) is an inhibitor of growth and virulence of pathogenic bacteria. To test for its effect on probiotic bacteria, WH was tested on the growth and biofilm formation of a commercially available probiotic Lactobacillus plantarum PS128. As these bacteria are aerotolerant, the experiments were carried out aerobically and in nutritionally inadequate/poor (nutrient broth) or adequate/rich (MRS broth) conditions. Interestingly, despite its negative effect on the growth and biofilm formation of pathogenic bacteria such as Staphylococcus epidermidis, WH promotes the growth of the probiotic bacteria in a nutritionally inadequate environment while maintaining their growth under a nutritionally rich environment. In the absence of WH, no significant biofilm is formed on the surfaces tested (polystyrene and alginate), but in the presence of WH, biofilm formation was significantly enhanced. These results indicate that WH may thus be used to enhance the growth and survival of probiotics.